2016
DOI: 10.3390/nu8110699
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Breast Milk Iodine Concentrations in Lactating Women in Western Australia

Abstract: Breast-fed infants may depend solely on an adequate supply of iodine in breast milk for the synthesis of thyroid hormones which are essential for optimal growth and cognitive development. This is the first study to measure breast milk iodine concentration (BMIC) among lactating women in Western Australian (n = 55). Breast milk samples were collected between 2014 and 2015 at a mean (±SD) of 38.5 (±5.5) days post-partum. The samples were analysed to determine median BMIC and the percentage of samples with a BMIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
2
16
0
5
Order By: Relevance
“…There is no scientific consensus on the BMIC that represents a sufficient iodine intake, and a wide range of BMIC values have been reported in areas with varying iodine sufficiency [ 3 , 29 , 40 ]. BMIC typically ranges from <50 µg/L in iodine-deficient areas [ 41 ] to 100–200 µg/L in areas with iodine sufficiency [ 3 , 29 , 40 , 42 , 43 ]. A recent metabolic balance study proposed an estimated average requirement (EAR) of 72 µg/L in breastmilk to infants from 2–5 months of age [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no scientific consensus on the BMIC that represents a sufficient iodine intake, and a wide range of BMIC values have been reported in areas with varying iodine sufficiency [ 3 , 29 , 40 ]. BMIC typically ranges from <50 µg/L in iodine-deficient areas [ 41 ] to 100–200 µg/L in areas with iodine sufficiency [ 3 , 29 , 40 , 42 , 43 ]. A recent metabolic balance study proposed an estimated average requirement (EAR) of 72 µg/L in breastmilk to infants from 2–5 months of age [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 35% of the lactating women in the study sample were not born in Norway; however, we found no differences in BMIC, UIC, or iodine intake related to country of origin. Jorgensen et al found that median BMIC was lower for Caucasian than for non-Caucasian women [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Як і для вагітної, для мате рі годувальниці підвищити надходження йоду із продуктами харчування є досить складним завданням, оскільки рекомендувати вживати більшу кількість ЙС неможливо, а морепро дукти цій особливій категорії населення не можна споживати частіше 3-4 разів на тиждень з огляду на високий вміст важких металів. [11]. Системний аналіз досліджень різних років переконливо доводить зв'язок між запрова дженням програм загальної обов'язкової йоди зації солі в країні та вмістом йоду в грудному молоці.…”
Section: мє маменко 1 на бєлихunclassified
“…2). [2,8,[11][12][13][14]. Вважається, що збільшити йодне надходження необхідно ще на етапі преграві дарної підготовки за три місяці до заплановано го зачаття, продовжувати сапліментацію весь період вагітності та годування грудьми.…”
Section: тому навіть у країнах із достатнім йоднимunclassified
“…It is estimated that 1.9 billion people live in areas of the world subject to subclinical iodine deficiency, which is important for cognitive development in infancy [ 6 ]. The study by Jorgenson and her colleagues demonstrates that, in Australia, with a food fortification program and the recommendation that pregnant women take 150 mcg iodine supplements daily, the iodine content of breastmilk is generally adequate [ 7 ].…”
mentioning
confidence: 99%